Implementasi Akuntansi Pembiayaan Akad Qardh Pada Perbankan Syariah - Zaki Perdana Mulia; Ersi Sisdianto (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
In financial and economic management activities, the term banking is often known, both conventional banking and Islamic banking. Islamic banking is a financial institution that plays an important role in managing people's funds. Islamic financial institutions generally have a variety of products offered to the public. In banking activities, there are two main functions of the bank, namely as a savings and loan institution. The purpose of this article is to discuss and analyze related to one of the Islamic bank products, namely loan products that apply the Qardh contract to Islamic financial institutions. The results of the study indicate that the implementation of the Qardh contract in Indonesia is adjusted to the pillars, qardh requirements, and shigat qardh. Qardh contract can be interpreted as a loan that must be returned in the same amount with a certain pre-agreed period. In other words, Qardh is a loan without profit. If it is technically reviewed, then this loan will be given to someone or a sharia financial institution to another person who is used for emergency or urgent needs. The implementation of sharia accounting with Qardh contracts in Indonesia is guided by Law Number 21 of 2008 concerning Sharia Banking in Article 35 paragraph (1) which states that in practice sharia banking is required to implement the 5C principles, namely character, capacity, capital, condition of economy, and collateral.